2010
DOI: 10.1111/j.1755-5922.2009.00119.x
|View full text |Cite
|
Sign up to set email alerts
|

RESEARCH: Effects of Long‐Term Disease‐Modifying Antirheumatic Drugs on Endothelial Function in Patients with Early Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is associated with enhanced atherosclerosis and impaired endothelial function early after the onset of the disease and cardiovascular (CV) disease represents one of the leading causes of morbidity and mortality. It is well known that disease modifying antirheumatic drugs (DMARDs) are able to improve the course of the disease and the quality of life of these patients, but little is known about the effects of DMARDs on CV risk and endothelial dysfunction. Our goal was to examine the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
47
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 60 publications
5
47
1
1
Order By: Relevance
“…CRP levels correlated with ESR and disease duration. Our results support both Turiel et al [22,30] and Surdacki et al studies [21,31] in terms of the relation between ADMA and inflammation. Surdacki et al displayed that neither ADMA nor SDMA (symmetric dimethylarginine) were correlated with the disease activity and inflammatory activation [21,31].…”
Section: Discussionsupporting
confidence: 82%
“…CRP levels correlated with ESR and disease duration. Our results support both Turiel et al [22,30] and Surdacki et al studies [21,31] in terms of the relation between ADMA and inflammation. Surdacki et al displayed that neither ADMA nor SDMA (symmetric dimethylarginine) were correlated with the disease activity and inflammatory activation [21,31].…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, while CIMT and stiffness are relatively stable, vasodilatation can be affected by many confounding factors, such as disease duration and patient age. Furthermore, the majority of our patients were taking immunosuppressive drugs, which have an antiinflammatory effect that potentially affected the atherosclerosis process and, therefore, our results (52,53). The main limitation of this study was the small number of patients; this, in itself, may be due to the low prevalence of SSc (between 3 and 24 cases per 100,000 subjects) (45,46) and the size of our cohort that, however, was similar to the size of other studies.…”
Section: Discussionmentioning
confidence: 84%
“…Twenty-five ERA patients who had not experienced any cardiovascular events were evaluated. It was found that DMARDs significantly decreased DAS-28 scores (from 6.0 ± 0.8 to 2.0 ± 0.7) and increased coronary flow reserve (27). In another study, following a 12-week therapy with infliximab, a TNF-α blocker, a significant decrease of DAS-28 scores and lowered ESR and CRP levels were demonstrated (28,29).…”
Section: Discussionmentioning
confidence: 84%